Making music with computers creative programming in Python - Manaris, Bill; Brown, Andrew R. (CRC, 2014)
"Preface The book in your hands is the result of more than a decade of independent and collaborative effort by the two authors and their computer- music associates. Combining computers and music has a long and fruitful heritage. Moreover, the ideas which underpin the connection between calculating and composing date back centuries. In the 21st century, computers and music are more closely aligned than ever before. In particular, computers have become indispensable in music making, distribution, performance, and consumption. This book introduces important concepts and skills necessary to make music with computers. It interweaves computing pedagogy with musical concepts and creative activities. It does this while maintaining a natural, steady increase in computational skills that are always motivated by creative musical contexts. This book is mainly intended for introductory computer science courses and for courses in the intersection of computing and the arts. However, it is naturally suited for self-study. It assumes little musical and programming experience; it introduces topics and concepts as they arise through motivating, and hopefully inspiring examples. This book addresses two trends in computing education: (1) the growing use of the Python language for teaching introductory programming, and (2) the increasing infusion of computational thinking into liberal arts courses, especially interdisciplinary offerings in computing and the arts. It does so by presenting computer music topics in an accessible manner for our two main target audiences:"..
Includes bibliographical references and index
Keywords: COMPUTERS / Programming Languages / General; COMPUTERS / Programming / Algorithms; MATHEMATICS / General; Computer composition; Python (Computer program language); Computermusik; Python -- Programmiersprache; Programmierung